RNA Synthesis in Temperature-Sensitive Mutants of Vesicular Stomatitis Virus - Unger, John T. (1973)
T-particle-free stocks of temperature-sensitive mutants representing the four Glasgow complementation groups of the Indiana serotype of vesicular stomatitis virus were used to study RNA synthesis at the permissive and nonpermissive temperatures of 31 and 39 C, respectively. Mutants selected from the four Glasgow complementation groups were characterized on the basis of particle and ribonucleoprotein formation. Intracellular RNAs were further characterized by polyacrylamide gel electrophoresis. ts G22 (group II) and ts G41 (group IV), previously characterized as RNA negative at the nonpermissive temperature, synthesized low levels of RNA which could not be attributed to contaminating levels of revertants. Furthermore, the levels of synthesis could not be reduced by the addition of cycloheximide. These data suggest that ts G22 (group II) and ts G41 (group IV) contain a thermally stable, virion-encapsidated transcriptase, but fail to amplify RNA synthesis due to a thermally labile function presumably necessary for the synthesis of viral RNA. ts G31, a group III mutant, synthesized intracellular RNA at amplified levels at the nonpermissive temperature. Intracellular ribonucleoprotein complexes were isolated in copious amounts; however, no particles corresponding in size to finished virions were observed. These data suggest a thermally labile maturation factor or envelope associated structural protein to be defective in ts G31 (group III). ts G11 (group 1) showed no detectable RNA synthesis at the nonpermissive temperature. These data suggest ts G11 (group I) contains a thermally labile component involved in early transcription. This group may contain a number of mutants defective in different components of the transcription apparatus, which may not complement in vivo because of the physical improbability of subunit exchange between virion particles of the incoming inoculum.